Characterizing the High Breast Cancer Incidence in Bacolod City, Philippines - Carandang, Jose Santos R., IV (Animo Repository, 2019)
This paper characterizes the high incidence of breast cancer in Bacolod City, Philippines. The methods of research involved (1) an epidemiological study; (2) a determination study on the environmental factors that cause breast cancer; and (3) a breast cancer behavioral study. A statistical analysis of the personal demography profile found significant indicators of the presence or absence of breast cancer in the areas of breastfeeding duration (p = 0.0029), age when they experienced first sexual intercourse (p = 0.0449), cancer cases in the family (p < 0.0001), incidence of smoking (p = 0.0322), and occupation (p < 0.0001). From an environmental perspective, data obtained from the Department of Environment and Natural Resources (DENR) Region 6 showed nothing of suspect. The sociological dimension found a correlation between stress and the presence or vulnerability of patients and their families to breast cancer incidences. The study likewise found that the women in the study incorporated a range of attitude and behavior that directly and indirectly aim to manage the strains of home and office works revolving around the confluence of (i) faith, (ii) their family, and (iii) and anticipated future. The study promotes the creation of breast cancer support groups as they present a positive and viable mechanism within the community to create social awareness about breast cancer and foster genuine social support networks for its members and their families as well as promote initiatives for low-income members to obtain medicines, referrals, and information. Investing in counseling for the survivors and their families leads to stress management and increased awareness about self-examination, increasing the probability of early detection. Overall, this study can serve as an important document that could be used by government agencies in drawing up screening as well as treatment and management programs for breast cancer in the Philippines.